Aquinas on ius and hart on rights: A response to tierney - Finnis, J (2002)
Of course Aquinas uses the term ius in an objective sense, to mean the just, the just thing, or the just state of affairs called for by the virtue of justice. But he also uses ius in a subjective sense, to refer to a right or rights that someone, the subject, has. Brian Tierney fails to see this, for three reasons, I think: though he has been an effective critic of Villey's historical analyses, he now seems gripped by Villey's non sequitur (if objective then not subjective); he looks to Aquinas's phrases, usages, and terms, sometimes neglecting the arguments in which Aquinas uses them; and, at least in this new essay, he employs a simplistic understanding of the modern idea of rights. Copyright © 2002 University of Notre Dame.